Persuasive communication and the diminution of the salt intake in heart failure patients: a pilot study - Mailson Marques de Sousa; Taciana da Costa Farias Almeida; Bernadete de Lourdes André Gouveia; Maria Eliane Moreira Freire; Francisco Stélio de Sousa; Simone Helena dos Santos Oliveira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to evaluate the effect of persuasive communication in the modulation of the behavioral intention of reducing the consumption of salt in heart failure patients. Methods: pilot quasi-experimental study with one group, before and after the application of audiovisual persuasive communication, as guided by the Theory of Planned Behavior. This study used a form built and validated to measure behavioral variables (Beliefs, Attitude, Subjective Norm, and Perceived Behavioral Control). Wilcoxon's test and Spearman's correlation were applied. Results: 82 heart failure patients who were being monitored in outpatient clinics participated. The medians of the behavioral variables increased significantly after the exposition to persuasive communication, showing a high level of intention to execute the behavior. Conclusions: persuasive communication positively contributed to influence the behavioral intention of reducing the consumption of salt in people with cardiac insufficiency.